2017
DOI: 10.1016/j.jenvman.2017.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Metal fractionation in sludge from sewage UASB treatment

Abstract: This study evaluates the trace metal composition and fractionation in sludge samples from anaerobic sewage treatment plants from six cities in Brazil. Ten metals were evaluated: Ni, Mn, Se, Co, Fe, Zn, K, Cu, Pb and Cr. Specific methanogenic activity of the sludge was also evaluated using acetic acid as the substrate. Among the essential trace metals for anaerobic digestion, Se, Zn, Ni and Fe were found at a high percentage in the organic matter/sulfide fraction in all sludge samples analyzed. These metals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…Few studies [2][3][4] attempted to fractionate trace elements in digested sewage sludge by chemical 38 sequential extraction procedures to determine the degree of leachability of different trace 39 elements' species. Zhu et al [4] underlined that sequential extraction methods could be used for 40 environmental risk assessment of digestate as a soil fertilizer.…”
Section: Matrix Interferences; 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies [2][3][4] attempted to fractionate trace elements in digested sewage sludge by chemical 38 sequential extraction procedures to determine the degree of leachability of different trace 39 elements' species. Zhu et al [4] underlined that sequential extraction methods could be used for 40 environmental risk assessment of digestate as a soil fertilizer.…”
Section: Matrix Interferences; 29mentioning
confidence: 99%
“…At the beginning and at the end of each experiment, an aliquot of digested sewage sludge was 178 sampled to measure the total and dissolved elements' content. About 5 g of raw sample (total 179 content) or 2 mL of supernatant (dissolved content), recovered after centrifugation at 3.000 g for 180 20 min, were digested with 6 mL of 69% HNO 3 Moreover, quality controls at 5 and 10 µg/L were added to check the performance of the analysis. 187…”
Section: Sample Treatment and Trace Elements Analysis 177mentioning
confidence: 99%
“…Due to a complex network of reactions, controlling the chemical speciation of TE, a small fraction of TE in the digesters environment is often available for microbial activities, while the majority of TE occur as precipitates, adsorbed or complexed species (Aquino and Stuckey, 2007;Maharaj et al, 2019Maharaj et al, , 2018. Several studies attempted to determine the fraction of TE available for uptake by microorganisms with sequential extraction procedures, such as the modified Tessier method (van Hullebusch et al, 2005) and the Community Bureau of Reference (BCR) method (Rauret et al, 1991) to guarantee an adequate supply of TE in digesters (Braga et al, 2017;Cao et al, 2018;Ortner et al, 2014). The procedure involves sequential treatment of the samples by chemical reagents such as neutral salts, weak and strong acids or reducing and oxidizing agents to selectively extract TE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sequential extraction methods are useful tools to assess mobility, accessibility, and potential bio-availability of TE (Harmsen, 2007). Braga et al (2017) observed that micronutrient TE, including Se, Zn, Ni and Fe were mainly found in the organic matter (OM)/sulfide fraction of the modified Tessier method applied on sewage sludge samples. Similar results were also found by Zufiaurre et al (1998) in sewage sludge samples.…”
Section: Introductionmentioning
confidence: 99%
“…Este produto secundário do tratamento pode estar contaminado por EPTs o que gera uma preocupação sobre a sua disposição final (Ahluwalia e Goyal, 2007;Yang et al, 2017). Os principais elementos encontrados no lodo de estações de tratamento de esgotos em regiões industrializadas do mundo são: o cádmio, chumbo, cobre, níquel e zinco (Chen et al, 2008;Shamuyarira e Gumbo, 2014;Braga et al, 2017;Östman et al, 2017;Yang et al, 2017 (Cai et al, 2007;Yang et al, 2017). O lodo de esgoto pode ser usado para recuperação energética, como fonte de extração de compostos, como por exemplo, a recuperação de fósforo ou pode ser tratado e usado em terra como fertilizante e condicionador de solo (Fijalkowski et al, 2017).…”
Section: Introductionunclassified